A large abdominal cyst in a neonate - Victor Juan Caraballoso Garcia; Marvin Fanny; Javier Rose; Michael Fayon (Elsevier, 2023)
Background: Gastrointestinal (enteric) duplication consists of a tubular or cystic structure that develops along the intestinal tube, with an estimated incidence of 1/10,000 in live births and 1/4500 in necropsies of neonates and fetuses. This congenital anomaly can appear in any portion of the intestinal tract; from the mouth to the rectum, with the ileum being the most common location. Case report: We herein report the case of a 5-day-old patient with a prenatal diagnosis of megacolon or mesenteric cyst. At laparotomy, a cystic mass attached to the terminal ileum was noted approximately 5 cm from the ileo-caecal valve. This mass was entirely resected and pathology studies classified the specimen as Type 1B intestinal duplication according to the Long classification. Discussion: Intestinal duplications are rare abnormalities of the embryological development of the gastrointestinal tract and usually present in childhood. The diagnosis can be made during antenatal follow-up. They can be asymptomatic or present with a variety of symptoms in relation to the location, the age of the patient or complications of the duplication. The diagnosis is suggested by abdominal X-rays and ultrasonography, and computerized axial tomography scan with contrast studies, but the definitive diagnosis is made by histopathological examination of the surgical specimen.